Mudanças climáticas e o protocolo de Quioto: desafios jurídicos e ambientais - Silva, Flávia Martins da (2012)
The problem of climate change is one of the major challenges faced by mankind. The situation of the greenhouse effect and the ozone layer hole is the foremost threat to human life. One of the key causes for this situation was the exploration and fossil fuels usage and the high rates of deforestation in the world, mainly in Brazil. The Kyoto Protocol, created during the Conference of the Parties nº III held in the city of Kyoto, Japan in 1997 with the purpose of supplementing the United Nations Framework Convention on Climate Change and establish a quantitative emission reduction limit of greenhouse gas (GHG) for countries under such Convention. At the present time the Kyoto Protocol is the only international climate agreement. The Protocol created flexibility mechanisms to achieve the ultimate goal of the Framework Convention, which is highlighted by the Clean Development Mechanism, which generated the carbon credits market. The mechanism for Reducing Emissions from Deforestation and Forest Degradation with increasing forest carbon stocks in developing countries (REDD) is currently a voluntary mechanism suggested by some countries that take part in the Convention, and recommended to assist developing countries to combat deforestation and degradation especially in tropical forests. The present paper aims to provide an overview of the trajectory of the Kyoto protocol in international environmental law, as well as demonstrate the importance and urgency of the matter of the problem of climatic changes.